The Role of Entrepreneurial Orientation, Knowledge Management, and Partnership on the Competitive Advantage - Putri, Intan Tsania; Sundawa, Afdholul Ihsan; Mahfudz, Mahfudz; Rahardjo, Susilo Toto (Research Horizon, 2024)
This research examines the influence of entrepreneurial orientation, knowledge management, and partnership strategy on business performance through competitive advantage in Batik Micro EnteIDRrises in Semarang City. Small businesses are crucial to the national economy, creating jobs and boosting the GDP. Yet, small batik businesses struggle with tough competition, lack of new product ideas, and limited market reach. We gathered information from 25 small batik businesses in Semarang City using a survey method. We analysed this data using statistical techniques, specifically the SEM PLS method with Smart-PLS 3.0 software, to test our research hypotheses. Our research shows that entrepreneurial mindset, knowledge management, and strategic partnerships positively impact competitive advantage, which in turn improves the performance of small batik businesses in Semarang City. The findings of this study underline the importance of strategic insight for Micro Business actors. in increasing the competitiveness of their business in order to compete with each other. Another contribution of this research can provide recommendations for the Government or related institutions in determining the approach to support the development of Micro Batik Businesses in Semarang City.